Effects of dried sugar beet root based concentrates level on wholesale cuts and eye muscle characteristics in Tagger male kids - Elimam, M. E.; Elshafie, N. O. H; Eltayeb, B. A; Ombabi, Y. A. (Gezira Journal of Agricultural Science; Vol 15 No 2 (2017), 2017)
Twelve Tagger males at 6 month old were used to study the effects of dried sugar beet root (DSBR) based concentrates level on animals performance, carcass and wholesale cuts characteristics. They were weighed and divided into 3 groups, each with 4 animals. They were housed in individual pens with feed and water troughs and allocated at random to the diets. They were weighed weekly for 8 weeks with a two weeks preliminary period. They were fed groundnut haulm (GNH) ad lib . in two equal meals at 8 am and 4  pm and different levels of DSBR based concentrates (0 (control), 150g and 300g) in two equal parts before GNH meals. The concentrates contained 68% DSBR,15% GNH cakes, 15% sunflower cake, 1% salt and 1% oyster shell. The animals were slaughtered, skinned and carcass characteristics were studied. The left side was divided into wholesale cuts and were weighed and dissected into muscle, fat and bone. The rib section (10 th – 12 th ) was removed and the characteristics and meat composition were determined. Percentages of best end of neck, breast and leg and chump, neck and loin generally increased with concentrates level. Concentrates level had no significant (P>0.05) effect on wholesale cuts percentages. Meat DM, CP, EE and ash were 32.82%, 17.3%, 2.15% and 3.0% at 0 concentrates, 37.5%, 17.9%, 2.35% and 2.65, respectively at 150g concentrates and 35.5%, 18.2%, 2.4% and 2.95%, respectively at 300g concentrates. Overall meat composition was 35.28%, 17.8%, 2.3% and 2.87%, respectively. Meat DM and CP varied significantly (P<0.05) with concentrates level. Animals fed no concentrates had the least DM, CP and EE and the highest ash. Animals fed 300g had the highest CP and EE. Supplementing GNH with DSBR based concentrates generally improved Tagger kids wholesale cuts percentages and meat composition. It is recommended to use DSBR based concentrates in fattening Tagger kids.         حفز ارتفاع الطلب وأسعار اللحوم في السودان على تحسين لحوم الماعز لارتفاع أعدادها وارتفاع العضلات والقيمة الغذائية وانخفاض الكولسترول والأحماض الدهنية المشبعة.  تعتبر التقر سلالة واعدة لإنتاج اللحوم لجودة القوام ونوعية اللحم. إنتاج اللحوم عامة تقليدي مع انخفاض الاستثمار والعائدات. التغذية من أهم المعوقات لتدهور المراعي والتباين الموسمي في كمية ونوعية العلف وغلاء العلائق المركزة . أدخل بنجر السكر لولاية الجزيرة وهو علف واعد خاصة الجذر لارتفاع الطاقة. لا تتوفر معلومات عن استخدام جذر البنجر الجاف لجديان التقر.  ولذلك أجريت هذه الدراسة لاختبار اثر مستويات عليقة مركزة ترتكز على جذر البنجر الجاف على الأداء وصفات الذبيحة وتركيب اللحم في جديان التقر. وضعت 12 من ذكور جديان التقر بعمر 6  أشهر في حظائر فردية بها أوعية للعلف والماء وأعطيت عشوائيا الأعلاف  المختبرة. وزنت الحيوانات أسبوعيا لمدة 8 أسابيع منها أسبوعين فترة إعدادية. أعلفت الحيوانات تبن الفول السوداني حسب الرغبة في وجبتين متساويتين عند الثامنة صباحا والرابعة مساء ووزن العلف المتبقي. أعلفت الحيوانات مستويات مختلفة من عليقة مركزة ترتكز على جذ و ر البنجر الجاف (صفر ( الشاهد)  150 و300جم ( في جزئين قبل وجبات تبن الفول السوداني . احتوت العليقة المركزة على 68% جذ و ر البنجر الجاف و15%  امباز فول سوداني و15%  أمباز زهرة الشمس و1% ملح و 1% صدف.  حفظت عينات من تبن الفول السوداني و جذ و ر البنجر الجاف والتبن المتبقي والعليقة المركزة للتحليل المعملي . ذبحت الحيوانات وسلخت  وفصلت مكونات الجسم الثانوية ووزنت لوحدها. وزنت الذبيحة وحسبت صفات الذبيحة.  قسم الجزء الأيسر من الذبيحة إلى قطع إجمالية ووزنت ثم شرحت كل منها.  فصلت العضلة العينية (الضلع 10-12 ) وعينت الصفات والتركيب .. قُسمت الذبائح لخمسة قطع تجارية ولم تُلاحظ فروق معنوية بين مستويات العلائق المركزة. عند التحليل الكيميائي للحوم كانت النسب المئوية للمادة الجافة و البروتين الخام والدهون الخام والرماد %32.82  و %17.3 و %2.15 و3.0  % للمجموعة القياسية و %37.5 و %17.9 و %2.35 و2.65 %عند 150 جم عليقة مركزة و  %35.5 و %18.2 و 2.4  2.95 % عند 300 جم عليقة مركزة ، علي التوالي. وكان المتوسط العام لتركيب اللحم %35.28 و %17.8 و2.3  %و %2.87 ، علي التوالي وكانت الفروق بين مستويات العليقة المركزة معنوية للمادة الجافة والبروتين الخام (P<0.05) . كان للمجموعة القياسية أقل مادة جافة وبروتين خام ودهون وأعلي نسبة رماد.  بينما نالت المجموعة المغذاة علي 300 جم عليقة مركزة أعلي بروتين خام ودهون.  عامة ساهمت إضافة تبن الفول السوداني والعلائق المركزة المعتمدة علي جذور بنجر السكر في تحسين نسب القطع التجارية وتركيب اللحم.  نوصي استخدام علائق بنجر السكر لتسمين جديان التقر